Leisure and Play: The Way of A Hopeful Life - LaBadie, Benjamin (Lumen et Vita, 2015)
Leisure and play are the cause and nature of Christian hope. Both address the world’s woundedness, needs, and desires by creating time and space for dignity, freedom, and stillness. This is my argument, and I will look at Josef Pieper’s Leisure, The Basis of Culture to show how leisure is a stillness in which human beings realize their importance within the harmony of the cosmos and the divine. Leisure allows humans to be receptive to the grace of God, and it gives them hope for what the fulfillment of God’s kingdom looks like. I will also look at the political philosopher, Michael Oakeshott, who wrote the essay “Work and Play.” From here, I will show how play coupled with leisure gives human beings hope because there are some activities done for their own sake because they are good in themselves. Human beings in their wounds, needs, and desires think that work, utility, and possession are what will fill their lacks. In reality, according to Oakeshott, a life solely dominated by work, utility, and possession ends up exacerbating these lacks because no fulfillment ever comes–the lack and desires only deepen and expand. It is like a man paying off his debt with more debt: the obligation to keep working to pay what you owe only expands and enslaves you to work more. Thus, leisure and play are the cause for Christian hope because they are done for their own sake. They heal wounds and fulfill human being’s deepest desires for dignity, love, and meaning.